If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2-(+5m)(-5)=40
We move all terms to the left:
(2-(+5m)(-5)-(40)=0
We multiply parentheses ..
(2-(-25m)-40=0
| (2-5m)(-5)=40 | | 4*(x^2)+12*(x)+9=0 | | 9x+6+3x=18-48+9x | | 4x+3x-9=8x-1 | | 655*23.50+15.75l=34954 | | 655*23.50+15.75a=34,954 | | x^2=12x=8x-4 | | 655*29.50+15.75a=34,954 | | 3(-5-4x)=-2(4+5x) | | -2(x+3)-5x=-34 | | 655(29.50)+15.75l=34954 | | 3(x+4=45 | | 2x=√12−x+3 | | 4x+40+x=90 | | -2x+15=3x+5 | | 3/4-1/2x=2 | | 3x+12=9x-84 | | x+20=5x+52 | | 3(-2)=2x+6 | | 2x-4=3+5 | | 6x-9=-41+10x | | (4-x)(1-x)^(2)+2-2x=0 | | 2x²+7x-198=0 | | -6-5x=-10+3x | | 2·x6=6·(x+3) | | x=1.2+7.8÷3(5) | | 2u+6=15 | | 6- X-3=3x+1 | | 6- 2x-3=(23)=x+1 | | y/21+383=410 | | 1.5a+22=a | | 3x=30* |